光音響効果を利用した骨導振動に関する基礎検討 - 和田森, 直 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
Conventional bone conduction earphones convert audio information into physical vibration using an oscillatory actuator to convey this vibration to the skin around the tragus. However, bone conduction earphones that actuate facial bones by audible band vibration easily leak sound to the air. When illuminated by modulated light, a sample is heated by a non-radiative transition. This generation of heat is modulated and can produce thermal and elastic waves inside the sample. We propose a bone conduction earphone system capable of conveying sound to the auditory organs through vibration using the photoacoustic effect. Herein, we describe the structure of the proposed system and its function.